(untitled) (Theatrum historiae, 2017)
The article is a case study based on two collections of letters between couples in Moravia during the Great War. Using these collections that include either both or – rather uniquely – only the woman’s side of the correspondence, the author tries to follow the basic strategies employed by respective parties to the wartime dialogue between the frontline and the home front, ranging from discursive silence to standardized “calming phrases” and strategies, all the way to the moments when these strategies crumble under the weight of the events. In parallel, the text also focuses on the way these strategies reflected the changing gender structures and relations in wartime society, particularly the sense of empowered femininity and weakened masculinity, respectively.